Prognostic Value of Residual Syntax Score Combined with Acef Score in Acute Coronary Syndrome Patient After Percutaneus Coronary Intervention in Saiful Anwar Hospital, Malang - Adhika Prastya Wikananda; Mohammad Saifur Rohman; Novi Kurnianingsih; Sasmojo Widito; Ardian Rizal (Universitas Brawijaya, 2022)
Background : Percutaneous coronary intervention (PCI) is one of the revascularization options in patients with clinical acute coronary syndrome (ACS) who often have multiple and complex vascular lesions. So, the decision to complete revascularization is still a topic that is widely explored to reduce the rate of rehospitalization and reinfarction. This study aims to determine the predictor value of rehospitalization and reinfarction events that can be used in ACS patients undergoing IKP using coronary angiography parameters with residual SYNTAX scores and clinical parameters using ACEF scores. Method : The study was cohort prospective with the inclusion criteria being all ACS patients who underwent PCI in RSUD Dr. Saiful Anwar Malang from January 2017 to July 2021. All patients underwent IKP and underwent coronary angiography evaluation after IKP with a residual SYNTAX score (rSS) and divided into categories into rSS≤8 and rSS>8. All patients underwent laboratory examination of serum creatinine and post-PCI echocardiography, and an ACEF score was obtained (ACEF score = age/left ventricular ejection fraction + 1 [if serum creatinine >2 mg/dl]). Research subjects will be followed up for at least 1 year related to the incidence of post-PCI rehospitalization and reinfarction. Results : From a total sample of 209 patients, it was found that the residual SYNTAX score data had the most significant predictive factor for the occurrence of rehospitalization at 1 year after PCI (OR 6.14 [95% CI, 1.92-1967]). At the value of rSS > 8, (AUC 0.750 [95% CI, 0.682-0.818], p 0.001) has a good predictive value for the occurrence of rehospitalization. However, combining with clinical parameters using the ACEF score provides a better predictive value. This study shows that the combination of rSS>8 and ACEF score>1.2 provides a better predictive value (AUC 0.884 [95%CI, 0.832-0.936) for the incidence of rehospitalization in post-PCI ACS patients. Conclusion : Acute coronary syndrome patients with residual SYNTAX scores > 8 and ACEF scores > 1.2 had a strong predictive value for rehospitalization events 1 year after PCI. The use of the combination of these two scores is expected to be a clinical guide to obtain the degree of completeness of revascularization in ACS patients.